DZIELIMY SIĘ DOŚWIADCZENIEMCardiac tamponade with acute hypovolaemic shock induced by a right ventricular lesion during implan-tation of a PHILOS SR cardiostimulator and a SELOX ST 60 ventricular electrode – a case report - Banyś, Andrzej; Bartczak, Karol; Bitner, Mirosław; Banach, Maciej; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
A cardiac (pericardial) tamponade (PT) is an acute, life-threatening condition induced by compression of the cardiac chamber, caused by rapid blood accumulation in the pericardial sac, resulting in reduced atrial and ventricular filling and subsequently cardiac output. Severe acute pericardial blood pressure can cause a drop in the haemodynamics (blood pressure), cardiac shock, abnormal heart rhythms or death. In the following article we present the case report of an acute, life-threatening cardiac tamponade with acute hypovolaemic shock, in an 80-year-old patient undergoing cardiostimulator and ventricular electrode implantation.